Impact of R&D Activities on the Friendly Degree of Traditional Medicines - Thanh Ha, Dinh (VNU Journal of Science: Policy and Management Studies; Vol 37 No 1DO - 10.25073/2588-1116/vnupam.4300, 2021)
In Vietnam, traditional medicine (TM) is an integral part of the national health care system. The social trend to return to products of natural materials is increasingly popular. Domestic consumers are very concerned about the following factors: treatment effectiveness, safety, price, convenience and package design of TM products. However, a preliminary survey showed, many domestic TM products were not highly appreciated by the TM practioners and consumers, and lacked competing capability with imported TM products. The reason is that domestic TM products still have such limitations: lack of quality stability, lack of diversity in types and design. Therefore, identifying tools which can help solve the problems of domestic TM products is necessary. This study aims to find out the impact of R&D activities on the friendly degree of traditional medicines, suggesting tools for domestic TM organizations to improve the quality and competitiveness of TM products. Keywords R&D activities, the friendly degree of traditional medicines. References [1] Martins Ekor, The growing use of herbal medicines: issues relating to adverse reactions and challenges in monitoring safety, Front. Pharmacol. , https://doi.org/10.3389/fphar.2013.00177, 10 January 2014 (accessed 11 March 2021). [2] Alternative Medicine: Complete Sector Overview. https://www.reportlinker.com/ci02242/Alternative-Medicine.html (accessed 11 March 2021). [3] P.V. Khanh, Developing sustainable medicinal materials in association with the development of traditional medicine, Proceedings of the Government's online conference on the development of Vietnamese traditional medicine, Lao Cai, 2017, p.157 (in Vietnamese). [4] National Istitute of Medicinal Materials, List of Vietnamese medicinal plants Science and Technology Publishing House, 2016 (in Vietnamese). [5] T.N. Ca, Research to make a policy linking 4 “houses”: state - entrepreneur - scientist - farmer, to develop and use effectively Vietnamese medicinal plants, Research project on social sciences and humanities 2011 - 2012 at ministerial level of the National Science and Technology Policy Council, 2012, p.77 (in Vietnamese). [6] OECD, Frascati Manual 2015: Guidelines for Collecting and Reporting Data on Research and Experimental Development, 2015, p.44. [7] D.T. Ha, Policy to develop Research and Development (R&D) activities to increase the friendly degree of traditional medicines to consumers (in Vietnamese), Doctoral thesis in Science and Technology Management, University of Social Sciences and Humanities/Vietnam National University, Hanoi, 2017. [8] Traphaco, http://www.traphaco.com.vn, 2016 (accessed 11 March 2021)